Biodegradable poly(lactide-co-glycolide-co-ε-caprolactone) block copolymers – evaluation as drug carriers for a localized and sustained delivery system. Issue 41 (17th September 2015) - Park, Ji Hoon; Kang, Hwi Ju; Kwon, Doo Yeon; Lee, Bo Keun; Lee, Bong; Jang, Ju Woong; Chun, Heung Jae; Kim, Jae Ho; Kim, Moon Suk
Abstract : To develop an appropriate drug carrier for drug delivery systems, we prepared random poly(lactide- co -glycolide- co -ε-caprolactone) (PLGC) copolymers in comparison to commercial poly(lactic acid- co -glycolic acid) (PLGA) grades. Abstract : To develop an appropriate drug carrier for drug delivery systems, we prepared random poly(lactide- co -glycolide- co -ε-caprolactone) (PLGC) copolymers in comparison to commercial poly(lactic acid- co -glycolic acid) (PLGA) grades. The molecular weights of PLGC copolymers varied from 20k to 90k g mol −1 in the total polyester segments, when poly-l -lactic acid (PLLA), polyglycolic acid (PGA), and polycaprolactone (PCL) compositions were kept constant. The lengths of PLGC copolymers varied from 10 : 10 : 80 to 40 : 40 : 20 in the PLLA : PGA : PCL segments, when the molecular weights of the total polyester segments were kept constant. The crystalline properties of the PLGA copolymers can be changed to amorphous by the incorporation of PCL segments. In vitro and in vivo degradation behavior can be easily tuned from a few days to a few weeks by changing the chemical composition of the PLGC copolymers. The in vivo inflammation associated with the PLGC implants was less pronounced than that associated with PLGA. In this study, as drug delivery carriers for locally implantable paclitaxel (Ptx) dosages, Ptx-loaded PLGC and PLGA films showed in vitro and in vivo Ptx release for 35 days. The orders of Ptx release showed profiles similar to those of in vitro and in vivo degradation of PLGC. Using near-infrared (NIR) fluorescence imaging, we confirmed the sustained release of NIR over an extended period from IR-780-loaded PLGC and PLGA implanted in live animals. In conclusion, we confirmed that compared to PLGA, PLGC effectively acts as a drug carrier for drug delivery systems.